Genetic drift precluded adaptation of an insect seed predator to a novel host plant in a long-term selection experiment. - Liisa Laukkanen; Aino Kalske; Anne Muola; Roosa Leimu; Pia Mutikainen (PLoS ONE, 2018)
Host specialization is considered a primary driver of the enormous diversity of herbivorous insects. Trade-offs in host use are hypothesized to promote this specialization, but they have mostly been studied in generalist herbivores. We conducted a multi-generation selection experiment to examine the adaptation of the specialist seed-feeding bug, Lygaeus equestris, to three novel host plants (Helianthus annuus, Verbascum thapsus and Centaurea phrygia) and to test whether trade-offs promote specialization. During the selection experiment, body size of L. equestris increased more on the novel host plant H. annuus compared to the primary host plant, Vincetoxicum hirundinaria, but this effect was not observed in other fitness related traits. In addition to selection, genetic drift caused variation among the experimental herbivore populations in their ability to exploit the host plants. Microsatellite data indicated that the level of within-population genetic variation decreased and population differentiation increased more in the selection line feeding on H. annuus compared to V. hirundinaria. We found a negative correlation between genetic differentiation and heterozygosity at the end of the experiment, suggesting that differentiation was significantly affected by genetic drift. We did not find fitness trade-offs between L. equestris feeding on the four hosts. Thus, trade-offs do not seem to promote specialization in L. equestris. Our results suggest that this insect herbivore is not likely to adapt to a novel host species in a time-scale of 20 generations despite sufficient genetic variation and that genetic drift disrupted the response to selection.